The disaster recovery handbook : a step-by-step plan to ensure business continuity and protect vital operations, facilities, and assets - Wallace, Michael, 1960- (AMACOM ; McGraw-Hill [distributor], 2011)
No organization is safe without a disaster recovery plan in place. Expanded and up to date, this is the ultimate resource.
Keywords: Emergency management -- Handbooks, manuals, etc.; Crisis management -- Handbooks, manuals, etc.; Computer security -- Handbooks, manuals, etc.; Data protection -- Handbooks, manuals, etc.; Data recovery (Computer science) -- Handbooks, manuals, etc.; Business planning -- Handbooks, manuals, etc.; elektronické knihy; electronic books